City regions and decent work: Politics, pluralism and policy making in Greater Manchester. (May 2023) - Johnson, Mathew; Martínez Lucio, Miguel; Mustchin, Stephen; Grimshaw, Damian; Cartwright, Jo; Rodriguez, Jenny K.; Dundon, Tony
Despite a growing body of literature examining the politics of city-regionalism, the question of how local actors engage with, and challenge each other in the subnational regulatory space requires greater attention if we are to develop a more comprehensive understanding of supposedly pluralist approaches to policy making. This paper critically evaluates policy innovations in Greater Manchester (GM) that seek to steer the behaviour of economic actors towards a mutually reinforcing model of decent work and social inclusion. We argue that underneath the expansive political agenda of the GM metro mayor, what has emerged so far is a relatively shallow form of consensus-based neo-pluralism that allows for elite consultation over issues of inclusive growth and responsible business rather than more radically redistributive or participatory policies. The implications for our understanding of the changing and often contradictory role of the state in shaping subnational regulation and governance are discussed.